ANALISIS PENERAPAN TATA KELOLA KORPORAT PADA INDUSTRI PRODUK TEKSTIL KECIL DAN MENENGAH DI PEKALONGAN - Nugraheni, Bernadetta Diana; Martono, Cyrillius (Jurnal Akuntansi Kontemporer, 2020)
A good management inside acompany will result a good performance and it is also applicable in small medium enterprise (SME). SME must implement good corporate governance (GCG) principle which are transparency, accountability, responsibility, independency, fairness and equality. The aim of this research is to study and analyze the implementation of the GCG which would be linked to those 5 principles mentioned before. The object of this research is taking sample of SME in textile industries in Pekalongan, Center of Java. With 96 respondents, using Cluster Analysis method and utilizing score table, it can be understood that the implementation of GCG in this industry is far below expectation which is around 50% and 48% who already implement it. The responsibility principle is the most implemented in this industry followed by independency, fairness and equality principle. Whereas transparency and accountability are the worst to be implemented. From the differentiating test it can be conclude that transparency principle is showing the most difference between all the respondents clusters.